Financial Technology Dan Literasi Keuangan Terhadap Generasi Z - Novianta, Erine; Andani, Ade; ., Fahriadi; Pane, Sanusi Ghazali (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The development of digitalization has changed consumer behavior among the younger generation, including in the economic sector with the presence of fintech. Access to economic activities provided is very effective, easy and fast. The aim of this research is to determine the influence of Fintech and financial literacy, especially on generation Z. The research method uses literature review studies in journals that are relevant to the discussion. The research results show that the development of fintech has a significant influence on generation Z's understanding of literacy. The use of fintech applications is widely used by the younger generation because it provides convenience and comfort in accessing various types of services and available facilities. Financial literacy plays an important role in making financial planning wiser and more productive to manage cash flow, savings, and credit ownership.